2024
DOI: 10.1002/wrna.1847
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs: Emerging regulators of behavioral complexity

Sanovar Dayal,
Divya Chaubey,
Dheeraj Chandra Joshi
et al.

Abstract: The mammalian genome encodes thousands of non−coding RNAs (ncRNAs), ranging in size from about 20 nucleotides (microRNAs or miRNAs) to kilobases (long non−coding RNAs or lncRNAs). ncRNAs contribute to a layer of gene regulation that could explain the evolution of massive phenotypic complexity even as the number of protein‐coding genes remains unaltered. We propose that low conservation, poor expression, and highly restricted spatiotemporal expression patterns—conventionally considered ncRNAs may affect behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 158 publications
0
1
0
Order By: Relevance
“…ncRNA, once deemed an insignificant component of the human genome, has emerged as a key player in cellular biology. This paradigm shift has revealed that ncRNAs, despite their lack of protein-coding capability, significantly influence various biological processes (Dayal et al 2024 ). LncRNAs are pivotal components of the non-coding RNA landscape and are essential in controlling different biological processes (Machlowska et al 2020 ; Chen et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…ncRNA, once deemed an insignificant component of the human genome, has emerged as a key player in cellular biology. This paradigm shift has revealed that ncRNAs, despite their lack of protein-coding capability, significantly influence various biological processes (Dayal et al 2024 ). LncRNAs are pivotal components of the non-coding RNA landscape and are essential in controlling different biological processes (Machlowska et al 2020 ; Chen et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%